Delta Force - Whiting, Jim, 1943- (Mankato, MN : Creative Education, 2014)
"A chronological account of the American military special forces unit known as Delta Force, including key details about important figures, landmark missions, and controversies"--
Disaster in the desert -- Only the toughest make the grade -- A global reach in fact and fiction -- A history of extraordinary accomplishments -- Glossary.
"A chronological account of the American military special forces unit known as Delta Force, including key details about important figures, landmark missions, and controversies."--Provided by publisher.
Includes bibliographical references and index.
Keywords: United States. -- Army. -- History -- Juvenile literature